The Effect of Tax Planning and Profitability on Company Value with Transfer Pricing as a Moderating Variable in Manufacturing Companies Listed on The Indonesian Stock Exchange - Ningsih, Hellen Wahyu; Fauziah, Satya (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study aims to analyze the effect of tax planning and profitability on company value with transfer pricing as a moderating variable in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Background Problems: Manufacturing firms in the food and beverage subsector are under pressure from rising production costs, volatile raw material prices, and more stringent tax laws. Investor worries regarding transfer pricing methods that could impact the value of the company have also been raised by the increase in related-party transactions. Novelty: This study is innovative in that it uses transfer pricing as a moderating element to examine how this variable affects the relationship between tax planning and profitability on corporate value. Research Methods: A quantitative strategy with a causal design was employed. Purposive sampling was used to collect samples, yielding a total of 120 samples from 30 companies between 2021 and 2024. Descriptive statistics, traditional assumption tests, and multiple linear regression utilizing the moderated regression analysis (MRA) method were used to examine the data. Findings/Results: The findings indicate that while profitability has no discernible impact on raising a company's worth, tax planning does. Although it can reduce the relationship between tax planning and company value, transfer pricing has a negative impact on company value. Transfer pricing, however, has little effect on how profitability and firm value are related. Conclusion: In conclusion, tax planning is a more effective strategy than profitability in increasing the transfer pricing value of a company, serving to strengthen this relationship when carried out in a reasonable and transparent manner.